Modeling of lower extremity forces in the dolphin kick - Jensen, R. K.; McIlwain, J. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
Little is known about the contribution of the dolphin kick to changes in the horizontal and vertical momentum of the swimmer. Counsilman (1968) asked if the dolphin kick is propulsive. He observed that the first kick may accelerate the swimmer and elevate the hips (p. 69). Data collected by Barthels and Adrian (1975) suggest that during the reach and early outsweep phases for the arms, the downbeat of the legs is accompanied by a forward acceleration of the hip. The horizontal and vertical forces produced by movement of the body segments through water can be estimated from modeling techniques. The purpose of this study was to model the lower extremity of the swimmer and to estimate the joint reaction forces for the dolphin kick. In the past, modeling studies of swimming strokes have been theoretical and were based on input functions for the motions of the segments. Analytical studies were done by Seireg and Baz (1971). Gallenstein and Huston (1973), Jensen and Blanksby (1975), and Jensen and Tihanyi (1978). These studies indicate the relative contributions of the segments to the stroke. In the present investigation empirical data were collected and used to estimate the segmental forces and moments offorce.